2006
DOI: 10.1175/bams-87-3-291
|View full text |Cite
|
Sign up to set email alerts
|

Can Lightning Observations be Used as an Indicator of Upper-Tropospheric Water Vapor Variability?

Abstract: The link between the daily variability of lightning and upper-tropospheric water vapor suggests a possible method of monitoring an important climatic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 29 publications
3
64
3
1
Order By: Relevance
“…Furthermore, since late afternoon in the three thunderstorm hot-spots occurs at different universal times (South America-2000 UTC, Africa-1400 UTC and Southeast Asia-0900 UTC), we can further separate the regions temporally, with three distinct maxima in thunderstorm activity observed in the diurnal cycle of the SR. Therefore, using our different detectors at different universal times, ELF radiation arriving from the African continent can be isolated (Price and Melnikov 2004;Price and Asfur, 2006). Since the magnetic field measurements are absolutely calibrated, the units in pico-Tesla (pT=10 −12 Tesla) provide a quantitative measure of lightning intensity.…”
Section: Data and Empirical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, since late afternoon in the three thunderstorm hot-spots occurs at different universal times (South America-2000 UTC, Africa-1400 UTC and Southeast Asia-0900 UTC), we can further separate the regions temporally, with three distinct maxima in thunderstorm activity observed in the diurnal cycle of the SR. Therefore, using our different detectors at different universal times, ELF radiation arriving from the African continent can be isolated (Price and Melnikov 2004;Price and Asfur, 2006). Since the magnetic field measurements are absolutely calibrated, the units in pico-Tesla (pT=10 −12 Tesla) provide a quantitative measure of lightning intensity.…”
Section: Data and Empirical Modelmentioning
confidence: 99%
“…It was recently shown (Price and Asfur, 2006) that African lightning intensity is highly correlated, on a daily time scale, with the amount of water vapor (specific humidity in g/kg) in the upper troposphere (near 300 mb∼10 km) above the African continent. It was demonstrated that lightning activity over tropical Africa results in the moistening of the African upper troposphere one day after the lightning activity.…”
Section: Data and Empirical Modelmentioning
confidence: 99%
“…Again for the 27 March 1997, the latent heat flux shows similar features (not shown here). From these records it is apparent that thunderstorm dissipation likely occurred between 12 and 15 UTC because the heat flux grew from 09 to 12 UTC [20], equatorial Africa is one of the three thunderstorm hot spot regions (South America, Africa, and Southeast Asia) where most thunderstorm events take place around 14.00 UTC. Therefore our observations are in agreement with previous finding.…”
Section: Resultsmentioning
confidence: 99%
“…Recent laboratory studies of arc discharges also indicate a large ratio of NO/NO 2 and minimal O 3 production [18]. According to Price [19] and Price and Asfur [20], equatorial Africa is one of lightning hot spot regions of the world. Marufu et al [21] showed that 27% of the troposphere O 3 abundance observed over Africa is caused by lightning induced nitrogen oxides (LNOx).…”
Section: Introductionmentioning
confidence: 99%
“…Recent laboratory studies of arc discharges also indicate a large ratio of NO/NO 2 and minimal O 3 production [26]. According to Price and colleagues [27,28], equatorial Africa is one of lightning hot spot regions of the world. Marufu et al [29] showed that 27% of the troposphere O 3 abundance observed over Africa is caused by lightning induced nitrogen oxides (LNOx).…”
Section: Introductionmentioning
confidence: 99%